2003
DOI: 10.1046/j.1365-2621.2003.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Technological characterization of lactic acid bacteria from Tenerife cheese

Abstract: One hundred and thirty lactic acid bacteria (Lactococcus, Lactobacillus and Leuconostoc), isolated from Tenerife cheese, were technologically characterized. Interesting differences within genera, species and strains were found. None of the strains showed lipolytic activity on tributyrin agar while the majority exhibited proteolytic activity on calcium caseinate agar. Citrate was metabolized exclusively by 98.3% of the lactobacilli isolates. Lactococcus lactis ssp. lactis showed the highest acidifying and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
7
18
0
4
Order By: Relevance
“…The low lipolytic activity, found in all strains tested, represents an important result and a useful contribution to aroma production, in agreement with other authors (Perez et al . ; Nieto‐Arribas et al . , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low lipolytic activity, found in all strains tested, represents an important result and a useful contribution to aroma production, in agreement with other authors (Perez et al . ; Nieto‐Arribas et al . , ).…”
Section: Discussionmentioning
confidence: 99%
“…paracasei strains, and this result was in agreement with other authors as regards the lactobacilli strains (Perez et al . ; Nieto‐Arribas et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a technological characterization of lactic acid bacteria from Tenerife cheese, Pérez, Cardell, and Zárate (2003) reported that none of the LAB strains showed lipolytic activity when assayed on tributyrin agar.…”
Section: Lipolytic Activitymentioning
confidence: 94%
“…The activities of greatest interest are those conferred by a single enzyme, ideally one with an extracellular localization. Such (294) Tripeptides (168) N-terminal pentapeptide of bradykinin (294,295) CBZ-amide-p-NA (294) Tetrapeptides (168) X-Pro-p-NA derivatives (171) Pentapeptides (168) X-Pro-X tripeptides (171) AMC derivatives (78,242) WC Casein-FITC (78,242) Cheddar cheese slurry peptides (197) ArAm derivatives (213,270) Milk protein (221) AMC derivatives (242,295) Casein ( Cheddar cheese slurry peptides (197) ArAm derivatives (270) Milk protein (8,58,64,221) Caprine and ovine curdled milk substrates (93) Caprine and ovine curdled milk protein (93) Caprine and ovine curdled milk peptides (93) Lactobacillus pentosus AMC derivatives (295) Dipeptides (294) Gluten (107) Tripeptides (2) Pro-AMC (295) ABZ-peptide-p-NA (294) N-terminal pentapeptide of bradykinin (294,295) BZ-peptide-p-NA (294) Peptide-p-NA derivatives (123) CD Casein (70,107) p-NA derivatives …”
mentioning
confidence: 99%